Pola adsorpsi pewarna azo oleh biosorben dari kulit pisang - Endang Widjajanti LFX; Marfuatun '; Dewi Yuanita (Jurnal Sains Dasar, 2013)
Abstract This study aims to determine the optimum mass, optimum agitation times and the   effect of the concentration of direct red dye was adsorbed by charcoal of ambon and kepok banana peels. And to determine the influence of activator concentration of NaOH on the adsorption capacity of ambon and kepok banana peels on the adsorption of direct red dye. The subject of this study is the ambon and kepok banana peels. The object of this study is the efficiency of adsorption. The parameters in this study are the mass of adsorbent, agitation times, dye concentrations, and the concentration of NaOH activator. Adsorption capacity of banana peels to direct red dye is determined by the difference of concentration before and after adsorption. The concentration of dye was determined using a spectrophotometer at an optimum wavelength of visible light. The result shows that the optimum mass and agitation time for direct red dye adsorption which are adsorbed by the charcoal both of ambon and kepok banana peels adsorbent is 0.5 grams per 50 mL of the adsorbate and 2 hours, respectively. Direct red dye concentration does not affect the efficiency of adsorption ambon banana peel charcoal but influences the efficiency of adsorption kepok banana peel charcoal. The greatest adsorption ability of ambon and kepok  banana peels are given by NaOH activator at 0.5 M and 1 M. Key words: banana peel, banana peel charcoal, direct red, agitation time